Trophic ulcers-Practical management guidelines - Puri, Vinita; Venkateshwaran, N; Khare, Nishant (Indian Journal of Plastic Surgery, 2012)
The management of patients with trophic ulcers and their consequences is difficult not only because it is a recurrent and recalcitrant problem but also because the pathogenesis of the ulcer maybe different in each case. Methodically and systematically evaluating and ruling out concomitant pathologies helps to address each patient′s specific needs and hence bring down devastating complications like amputation. With incidence of diabetes being high in our country, and leprosy being endemic too the consequences of neuropathy and angiopathy are faced by most wound care specialists. This article presents a review of current English literature available on this subject. The search words were entered in PubMed central and appropriate abstracts reviewed. Relevant full text articles were retrieved and perused. Cross references from these articles were also reviewed. Based on these articles and the authors′ experiences algorithms for management have been presented to facilitate easier understanding. It is hoped that the information presented in this article will help in management of this recalcitrant problem.
Keywords: Diabetic ulcer; off-loading pressure; plaster boot; trophic ulcer